1978
DOI: 10.1021/jm00210a029
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of 1,2-diaminocyclohexaneplatinum complexes against Sarcoma-180 ascites form

Abstract: Platinum complexes derived from three isomers of 1,2-diaminocyclohexane have been synthesized and their antitumor activities were evaluated against ascites Sarcoma-180. All the platinum complexes had high antitumor activity. Platinum complexes derived from cis-1,2-diaminocyclohexane were more effective than those derived from trans-l-and trans-d-1,2-diaminocyclohexane. Among the platinum complexes tested, oxalato(cis-1,2-diminocyclohexane)platinum had a remarkably high therapeutic index. Modification of the no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
103
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(105 citation statements)
references
References 2 publications
1
103
0
1
Order By: Relevance
“…Kidani and co-workers have reported that platinum complexes with l,2-diaminocyclohexane, having different configurations at the two chiral carbons bridging the two nitrogens, had biological activities dependent on the chirality of the diamine ligand (30)(31)(32)(33). Although the isomers with R,R and S,S configurations at the asymmetric carbons produce the same type of intra-and interstrand cross-links (34), the biological activity of the two enantiomers is different, and the R,R enantiomer exhibits higher antitumor activity and lower mutagenicity than the S,S isomer (35).…”
Section: Chiral Discrimination In Platinum Anticancer Drugsmentioning
confidence: 99%
“…Kidani and co-workers have reported that platinum complexes with l,2-diaminocyclohexane, having different configurations at the two chiral carbons bridging the two nitrogens, had biological activities dependent on the chirality of the diamine ligand (30)(31)(32)(33). Although the isomers with R,R and S,S configurations at the asymmetric carbons produce the same type of intra-and interstrand cross-links (34), the biological activity of the two enantiomers is different, and the R,R enantiomer exhibits higher antitumor activity and lower mutagenicity than the S,S isomer (35).…”
Section: Chiral Discrimination In Platinum Anticancer Drugsmentioning
confidence: 99%
“…It must also be mentioned that oxaliplatin, a platinum‐based antineoplastic agent used for colorectal cancer was discovered by Kidani et al 55. in 1976.…”
Section: Colorectal Surgerymentioning
confidence: 99%
“…DACHPt has shown a wide and markedly different spectrum of activities than CDDP, such as lower toxicity than CDDP and no cross-resistance to it in many CDDP-resistant cancers (Rixe et al 1996;Zhang & Lippard 2003). However, DACHPt is significantly less soluble in water than CDDP (Kidani et al 1978). To enhance the water solubility of DACHPt as well as pinpoint delivery, DACHPt-loaded micelles were developed by metal complexation between platinum and carboxylic acids contained in a PEG-PGlu block copolymer (figure 4; Cabral et al 2005).…”
Section: Polymeric Micelles Delivering Anti-cancer Drugsmentioning
confidence: 99%